(untitled) (Research, Society and Development, 2020)
Selenium and Mercury are two chemical elements studied in several fields of knowledge due to their chemical properties and interactions. The aim of this study was to analyze the evolution of research activity from 1700 to 2017 on the global trend of these elements, we carried out a bibliometric analysis using the Scopus database. For each keyword accessed (“selenium”, “selenide”, “selenite”, “selenate”, “organoselenium”, “mercury”, “inorganic mercury”, “mercury vapor” and “methylmercury”), we analyzed the publication output, and the top 5 geographic distribution of publications and contributing authors, as well as the top 5 Scopus subject categories where the documents are indexed. The results demonstrated an increase in the number of publication over time for all the keywords. Research about Selenium and its inorganic and organic chemical forms, and Mercury and its inorganic and organic chemical forms were described in approximately 117,000 and 164,000 documents, respectively. United States was the country with the highest number of published documents in all the keywords analyzed. Chemistry, Medicine and Environmental Science were the subject categories with the highest number of documents. Researchers from the United States, China, Japan, Slovenia, and Brazil were in the ranking of the most productive authors. To our knowledge, this is the first bibliometric study on Selenium and Mercury and can be useful to identify potential research groups for scientific collaborations.